Studies for lipase production ability of Aspergillus sp. strains from the misiones rainforest of paranaense - Ortellado, Laura Ester (2025)
Fungi of the Aspergillus genus synthesize lipases, which are primarily extracellular enzymes secreted into the culture medium. These lipases have broad substrate specificity and are capable of hydrolyzing a variety of lipids, including triglycerides, phospholipids, and cholesterol esters, making them the focus of many studies on their applications. The present work carried out an exploratory analysis of the production of lipases in six fungi of the genus Aspergillus isolated in the Misionera Paranaense jungle (Argentina). Using simple qualitative detection techniques with tween 80% and rhodamine B as substrates, and based on the quantitative analysis carried out, it was determined that the isolate Aspergillus sp. LBM 054 showed the highest levels of lipase activity, reaching a total of 133 U/mL. A Plackett-Burman statistical test revealed that adding tributyrin to the culture medium significantly increased the activity of the lipase enzyme (p < 0.05), reaching a value of 168 U/mL. Among the concentrations evaluated, the addition of 2% tributyrin demonstrated the greatest increase in lipase activity, reaching a five-fold increase compared to the initial activity observed at the beginning of the assays. Optimum activity and stability at neutral to alkaline pH values make these enzymes suitable for various biotechnological applications. The zymogram of the selected strain showed an enzymatic profile that included a protein with a molecular mass of 38 kDa.